MindRegulation: randomized controlled trial of the effects of a relaxation and guided imagery intervention on the psychophysiological well-being, socioemotional regulation, cognitive and academic development of children in school - Galinha, Iolanda Costa (2024)
Background: Mental imagery has long been used in psychological therapies, but only recently did research begin to provide a scientific background for it.Imagery interventions are inexpensive anda substantial body of research supports their effectiveness on behavior change, promotion of adaptive health outcomes, anxiety reduction, and adherence to medical interventions, in both adults and children. However, literature on relaxation and guided imagery interventions benefits for children in elementary school context is very scarce. This Randomized Controlled Trial (RCT) aims to contribute to that knowledge by implementing and testing the benefits of an intervention program MindRegulation (MR) comprising relaxation, instructions for body posture, and guided imagery with socioemotional learning (SEL), conveying adaptive beliefs about oneself, the relationships with others and the environment. Method: The MR intervention will be developed in the classroom for 15 minutes before learning activities, three times per week, for five months, and its effects will be measured on a range of emotional, physiological, and cognitive outcomes. Fifteeen classes will be randomly assigned to three conditions: (a) relaxation and guided imagery-MR; (b) relaxation only; and (c) waitlist control. The RCT includes four data collection times: pretest, intermediate, posttest, and a six-month follow-up (trial registration NCT06101225, 05th October, 2023). The sample comprises 240 students, elementary school third and fourth graders, 8–11 years old. The variables measured in all times, except the intermediate, are: well-being, affect, anxiety, emotional regulation, socioemotional competencies, attention and processing speed, and perceived benefits of the intervention. Physiological indicators of emotional arousal, emotional regulation, stress and well-being are also taken, specifically, heart rate variability, electrodermal activity, actigraphy and salivary cortisol. The validity of the measures will be tested for the population and objectives of the study. Discussion: Significant improvements on the children's well-being, socioemotional regulation, cognitive function, physiological activity and academic performance are expected - after 5-months’ intervention at posttest and11 months’ follow-up -at MR condition, compared to the relaxation and control conditions. Changes in physiological activity are expected during MR and relaxation sessions. Emotional regulation, well-being and anxiety are expected to mediate the effects of the interventions over socioemotional competence, cognitive function and academic performance. Well-being and anxiety levels at pretest are expected to moderate the interventions’ effects.